تصوف میں تزکیہ نفس کی ضرورت واہمیت قرآن وحدیث کی روشنی میں: The purification of Soul(Tazkia e Nafs) (Khairulummah, 2021)
This article elaborates the essence and value of Tazkia. The importance of Tazkia (The purification of Soul) may be known from the fact that Allah Ta,ala in the Holy Quran, emphasizedit with seven oaths and said: (He has succeeded who purifies it). Moreover, all the prophets (Peace be upon them) invited the people towards the same thing (The purification of Soul). For example, Moses told Pharaoh:  (Would you (be willing to) purify yourself?).Allah said in the Holy Quran, regarding the Holy Prophet (Peace be upon Him): (2(It is He who has sent among the unlettered a Messenger from themselves reciting to them His verses and purifying them and teaching them the Book and wisdom although they were before in clear error).The purification of Soul (Tazkia) is the source of high degrees and perpetual blessings. The Holy Quran clarifies: But whoever comes to Him as a believer having done righteous deeds, for those will be the highest degrees. Gardens of perpetual residence beneath which river flow, wherein they abide eternally, and that is the reward of one who purifies himself.)The Holy Prophet (Peace Be Upon Him) also would pray: (O my God: give my soul righteousness and purify it, because You are the best one who can purify it, You are its Protector and Lord.